Archaeology and acrimony: Gertrude Bell, Ernst Herzfeld and the study of pre-modern Mesopotamia - Cooper, Lisa (Iraq, 2013)
Letters sent from the German scholar Ernst Herzfeld to Gertrude Bell between 1909 and 1912 provide valuable information about the scholarship of these remarkable characters as they explored issues pertaining to the development of early Islamic art and architecture in Mesopotamia. Through a spirited and often fractious exchange of ideas about a range of artistic and architectural topics that included vaulting techniques, the design of early mosques and palace forms, one can track the impact each had upon the other's scholarship, and the degree to which their respective views shaped one another's conclusions about important Islamic period sites such as Samarra and Ukhaidir.